Disability Identity in Older Age? - Exploring Social Processes that Influence Disability Identification with Ageing - Leahy, Ann (Disability Studies Quarterly, 2023)
While there is much debate about a disability identity, this does not apply to the identification processes of people experiencing impairment or disability first in older age, who are often assumed not to identify with a disability identity. This article aims to deepen understanding of the elements affecting identification with disability when impairment is experienced first in older age and their interplay. It does so by discussing findings from a new empirical study drawing on data from interviews with people first experiencing impairment with ageing and by engaging with scholarship from both critical studies on ageing and on disability. The findings discussed show that the issue of a disability identity in older age is more complex and fluid than has heretofore been assumed and that identity is always subject to renegotiation. It points to the role of dominant and binary discourses of ageing, and separate policy frameworks and approaches to activism on ageing and on disability, in constructing (or failing to construct) a ‘disability’ identity in older age. The article argues for greater linkages between the fields of ageing and disability in scholarship and advocacy and suggests that this offers potential to make the issue of ableism more broadly understood and resisted. It calls for more engagement by disability scholars with what disability experienced in older age illuminates about culture and with the implications of disability becoming a more widespread phenomenon due to population ageing.